The impact of organizational and professional development on human resource development practitioners in Malaysian organizations - Mohd Salleh, Kahirol; Sulaiman, Nor Lisa (Academic Research Publishing Group, 2019)
Competencies are skills set required for effective working performance in a real-world’s task or activity at the workplace. To develop competent workers in organizations, Human Resource practitioners need to establish training and development for their workers. In the context of an organization, organizational and professional development refers to any types of educational experiences, learning opportunities and competencies related to workers’ task. This paper provides an overview and framework for designing effective organizational and professional development systems towards better workers’ competencies. A non-experimental, descriptive, cross-sectional, web-based survey design was used to examine structure, process, and outcome variables associated with organizational and professional development. The findings suggested that HRD practitioners perceived the importance of organizational and professional development with regard to workers’ developmental process and organizational performance.